Gastric cancer chemotherapy - Notejane, R; Viola, A.; Musé, I M (Cirugía del Uruguay, 1988)
Gastrointestinal carcinomas were considered until a few years ago as low or poor chemosensitivity. However, adenocarcinomas gastric muscles begin to mark a change in these concepts. This change arises from having evaluated new cytostatic agents in patients with better general condition and taken in earlier stages Of his sickness.